Remote Control of Intestinal Stem Cell Activity by Haemocytes in Drosophila - Chakrabarti, Sveta; Dudzic, Jan Paul; Li, Xiaoxue; Collas, Esther Jeanne; Boquete, Jean-Phillipe; Lemaitre, Bruno (PLoS genetics, 2016)
The JAK/STAT pathway is a key signaling pathway in the regulation of development and immunity in metazoans. In contrast to the multiple combinatorial JAK/STAT pathways in mammals, only one canonical JAK/STAT pathway exists in Drosophila. It is activated by three secreted proteins of the Unpaired family (Upd): Upd1, Upd2 and Upd3. Although many studies have established a link between JAK/STAT activation and tissue damage, the mode of activation and the precise function of this pathway in the Drosophila systemic immune response remain unclear. In this study, we used mutations in upd2 and upd3 to investigate the role of the JAK/STAT pathway in the systemic immune response. Our study shows that haemocytes express the three upd genes and that injury markedly induces the expression of upd3 by the JNK pathway in haemocytes, which in turn activates the JAK/STAT pathway in the fat body and the gut. Surprisingly, release of Upd3 from haemocytes upon injury can remotely stimulate stem cell proliferation and the expression of Drosomycin-like genes in the intestine. Our results also suggest that a certain level of intestinal epithelium renewal is required for optimal survival to septic injury. While haemocyte-derived Upd promotes intestinal stem cell activation and survival upon septic injury, haemocytes are dispensable for epithelium renewal upon oral bacterial infection. Our study also indicates that intestinal epithelium renewal is sensitive to insults from both the lumen and the haemocoel. It also reveals that release of Upds by haemocytes coordinates the wound-healing program in multiple tissues, including the gut, an organ whose integrity is critical to fly survival.